Aminoglycoside Conjugation for RNA Targeting: Antimicrobials and Beyond. Issue 54 (10th August 2020) - Aradi, Klara; Di Giorgio, Audrey; Duca, Maria
Abstract: Natural aminoglycosides are therapeutically useful antibiotics and very efficient RNA ligands. They are oligosaccharides that contain several ammonium groups able to interfere with the translation process in prokaryotes upon binding to bacterial ribosomal RNA (rRNA), and thus, impairing protein synthesis. Even if aminoglycosides are commonly used in therapy, these RNA binders lack selectivity and are able to bind to a wide number of RNA sequences/structures. This is one of the reasons for their toxicity and limited applications in therapy. At the same time, the ability of aminoglycosides to bind to various RNAs renders them a great source of inspiration for the synthesis of new binders with improved affinity and specificity toward several therapeutically relevant RNA targets. Thus, a number of studies have been performed on these complex and highly functionalized compounds, leading to the development of various synthetic methodologies toward the synthesis of conjugated aminoglycosides. The aim of this review is to highlight recent progress in the field of aminoglycoside conjugation, paying particular attention to modifications performed toward the improvement of affinity and especially to the selectivity of the resulting compounds. This will help readers to understand how to introduce a desired chemical modification for future developments of RNA ligands as antibiotics, antiviral, and anticancer compounds. Abstract : Making connections : This review highlights recent progress in the synthesis of aminoglycoside conjugates directed against therapeutically relevant RNAs. Chemical conjugation of these widely employed antibiotics to different moieties allows for better affinity, selectivity, and biological activity in antimicrobial, antiviral, and anticancer fields of research.